THE DIAGNOSTIC AND PROGNOSTIC VALUE OF RIGHT VENTRICLE SYSTOLIC AND DIASTOLIC FUNCTION IN INFERIOR MYOCARDIAL INFARCTION - Purwaningtyas, Niniek (Biomedika, 2018)
Right ventricular (RV) involvement increases mortality and morbidity in inferior myocardial infarction (MI). There are sparse data on the usefulness of pulsed tissue Doppler imaging (TDI) in the diagnosis of RV dysfunction in ST segment elevation MI (STEMI). This study evaluate the diagnostic and prognostic significance of RV systolic and diastolic function compared to classical electrocardiographic RVMI diagnostic criteria in this group of patients. Consecutive patients with first, acute, inferior STEMI were prospectively assessed. The RVMI was defined as an ST-segment elevation ≥ 0.1 mV in lead V4R. Echocardiography with TDI was performed within24 h of the onset of symptoms. Out of 31 patients (mean age 56.39 ± 9.02 years), RVMI was found in 18 (37%). Multivariate analysis showed that two variables—RV systolic and diastolic function, were independent predictors of in-hospital prognosis. Sensitivity and specificity the RV systolic function were 94,4% and 69,2%, respectively. While RV diastolic function were 44% and 76,9%, respectively. RV systolic function predict ECG diagnosis of RVMI with relatively high sensitivity and specificity. RV diastolic function predict ECG diagnosis of RVMI with relatively low sensitivity but with high specificity.Keywords: tissue Doppler imaging, RV myocardial infarction, inferior myocardial infarction